2009
DOI: 10.18061/1811/36603
|View full text |Cite
|
Sign up to set email alerts
|

A Simpler Explanation for Vestibular Influence on Beat Perception: No Specialized Unit Needed

Abstract: Some researchers have hypothesized the existence of a specialized brain unit for beat perception in music which is directly influenced by vestibular stimulation arising from motion. They also suggest that the unit is involved in the entrainment of movement to music. However, the data used to support this hypothesis may be explained by a simpler phenomenon: the audiogravic and audiogyral effect. This effect is not related to beat perception at all but deals with perceived sound changes under accelerations. If t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…More critically it was demonstrated that head movement and therefore activation of the vestibular apparatus was necessary to observe the effect (Phillips-Silver and Trainor, 2007 ), and further that vestibular influence could be achieved directly by using galvanic vestibular stimulation (Trainor et al, 2009 ). However, the matter remains controversial, with some authors suggesting that the vestibular influence is not direct (Trainor, 2007 ; Riggle, 2009 ; Trainor and Unrau, 2009 ).…”
Section: Subsequent Developmentsmentioning
confidence: 99%
“…More critically it was demonstrated that head movement and therefore activation of the vestibular apparatus was necessary to observe the effect (Phillips-Silver and Trainor, 2007 ), and further that vestibular influence could be achieved directly by using galvanic vestibular stimulation (Trainor et al, 2009 ). However, the matter remains controversial, with some authors suggesting that the vestibular influence is not direct (Trainor, 2007 ; Riggle, 2009 ; Trainor and Unrau, 2009 ).…”
Section: Subsequent Developmentsmentioning
confidence: 99%
“…In other words, rhythm perception is a form of vestibular perception, even without overt head movement. However, the matter remains controversial, with some authors suggesting that the vestibular influence is not direct (Phillips-Silver and Trainor, 2007;Riggle, 2009;Trainor and Unrau, 2009). A further unresolved issue concerns what specific properties of the vestibular system, compared with other sensory systems, account for its role in rhythm perception.…”
Section: The Vestibular Syncopation Hypothesismentioning
confidence: 99%
“…In other words, rhythm perception is a form of vestibular perception, even without overt head movement. However, the matter remains controversial, with some authors suggesting that the vestibular in uence is not direct (Riggle, 2009;Phillips-Silver & Trainor, 2007;Trainor & Unrau, 2009). A further unresolved issue concerns what speci c properties of the vestibular system, compared with other sensory systems, account for its role in rhythm perception.…”
Section: The Vestibular Syncopation Hypothesismentioning
confidence: 99%